HUBUNGAN BEBAN KERJA DAN BURNOUT DENGAN PERILAKU CARING PADA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT PALANG BIRU GOMBONG - Kaunang, Natasha Rachel Oeyanda; Heri Susanti, Indri; Sumarni, Tri (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2023)
Caring is a holistic care action to support the patient's recovery. Caring can be influenced by physical factors (workload) and psychological factors (burnout). The purpose was to determine whether there is an influence between workload and burnout on caring. This research used a quantitative method with a cross sectional approach involving 45 nurses and 45 patients. The instruments in this research were caring behavior inventory 24-item, workload questionnaire, and maslach burnout inventory. Analysis of the data in this study used the Spearman rank test. Caring analysis showed 51.1% of nurses were caring with a high workload of 68.9% and 48.9% of nurses felt burnout. The results of Spearman's rho analysis results showed that there is a significant relationship between workload and caring behavior, p value = 0.007 and cc -0.399. Between burnout and caring behavior, p value = 0.001 and cc -0.466.. It is recommended for hospitals, especially the management team, to pay more attention to the workload and make sharing sessions between nurses and simulation of caring to incresed services. Keywords: caring behavior, workload, burnout